Prevalence and Departmental Variations of Work-Related Musculoskeletal Disorders among Electricity Distribution Workers - Omotunde Muyiwa; F. T. Akinremi (The Indonesian Journal of Community and Occupational Medicine, 2026)
Introduction: Electricity distribution workers are exposed to occupational hazards that may cause Work-related Musculoskeletal Disorders (WMSDs). However, studies are sparse on the departmental variation of the prevalence of WMSDs among the electricity workers in Nigeria. Objective: To examine the prevalence and departmental variations of WMSDs among Ibadan Electricity Distribution Company (IBEDC) employees. Method: A descriptive cross-sectional survey was conducted among 240 employees from three different departments across five service hubs of IBEDC. Demographic and WMSDs data were collected using a standardised Nordic musculoskeletal questionnaire. Data were analysed using percentages, descriptive statistics, and regression at to examine departmental variations. Result: Customer service worker reported highest WMSDs prevalence in the past 7days and 12months at lower back (10.9 and 23.0%), knees (9.6 and 20.4%), hips/thighs (8.3 and 17.8%), ankles/feet (7.4 and 16.5%), and neck (7.4 and 16.5%), respectively, followed by technical, and then administrative staff. The body areas that prevented most of the employees from working were the lower back, knees, upper back, and ankles/feet across departments. The findings revealed a statistically significant (p<0.05) difference between departments in variations of prevalence of the WMSDs among the workers. Conclusion: The prevalence of work-related musculoskeletal disorders was found to be common among customer service workers but significantly varied across the three departments. Ergonomic interventions, job redesign, and health education programs based on the department are required to minimise musculoskeletal symptoms.